Mortality in infantile spasms: A hospital‐based study. (5th March 2020) - Harini, Chellamani; Nagarajan, Elanagan; Bergin, Ann M.; Pearl, Phillip; Loddenkemper, Tobias; Takeoka, Masanori; Morrison, Peter F.; Coulter, David; Harappanahally, Gita; Marti, Candice; Singh, Kanwaljit; Yuskaitis, Christopher; et al.
Abstract: Objective: To determine risk factors and causes for mortality during childhood in patients with infantile spasms (IS). We describe the overall goals of care for those who died. Methods: This is a retrospective chart review of IS patients born between 2000 and 2011. We examined potential risk factors for mortality, including etiology, neurologic impairment, medication use, persistence of epileptic spasms, and comorbid systemic involvement (requirement for G‐tube feedings, respiratory interventions). For patients who died, we describe cause of death and resuscitation status or end‐of‐life care measures. Results: We identified 150 IS patients with median follow‐up of 12 years. During the study period, 25 (17%) patients died, 13 before 5 years of age. Univariate analysis demonstrated that developmental delay, identifiable etiology, hormonal use for IS, persistence of epileptic spasms, polypharmacy with antiseizure medications, refractory epilepsy, respiratory system comorbidity, and the need for a G‐tube were significant risk factors for mortality. In a multivariate analysis, mortality was predicted by persistence of epileptic spasms (odds ratio [OR] = 4.30, 95% confidence interval [CI] = 1.11‐16.67, P  = .035) and significant respiratory system comorbidity (OR = 12.75, 95% CI = 2.88‐56.32, P  = .001). Mortality was epilepsy‐related in one‐third of patients who died with sudden unexpected death in epilepsy (SUDEP), accounting for 88% of epilepsy‐related deaths. Most deaths before age 5 years were related to respiratory failure, and SUDEP was less common (17%) whereas SUDEP was more common (45%) with deaths after 5 years. For the majority (67%) of patients with early mortality, an end‐of‐life care plan was in place (based on documentation of resuscitation status, comfort measures, or decision not to escalate medical care). Significance: Mortality at our single‐center IS cohort was 17%, and persistence of epileptic spasms and comorbid respiratory system disorders were the most important determinants of mortality. Early deaths were related to neurological impairments/comorbidities. SUDEP was more common in children who died after 5 years of age than in those who died younger than 5 years.